Photoelectrical characteristics of novel Ru(II) complexes based photodiode - Farooq, W. A.; Elgazzar, Elsayed; Dere, A.; Dayan, O.; Serbetci, Z.; Karabulut, Abdulkerim; Hanif, Atif (Springer, 2019)
The Ru(II) complex was prepared by the reaction of 4-chloro-N-[(E)-(pyridin-2-yl) methylidene] benzene-1-sulfonamide, [RuCl2(p-cymene)](2) and 2,2-(pyridine-2,6-diyl) bis(1H-benzimidazole) compounds by simple chemical technique. Al/ruthenium(II) complex/p-Si/Al was characterized by electronic devices and its electrical properties were studied as photodiode. In dark, the photodiode parameters such as potential barrier phi and ideality factor n were investigated from current-voltage (I-V) plot and confirmed by using Cheung-Cheung and Norde's models. Under illumination effect, the synthesized device shows high photosensitivity and the charge carriers increased based on the trapped state created under the conduction band. It was observed from conductance-voltage (G-V) and resistance-voltage (R-s-V) measurements that the series resistance Rs of the diode is decreased dramatically and its conductance G is increased by applied electric field.
Keywords: Electrical Characteristics; Series Resistance; Solar-Cells; Diodes; Capacitance; Sensitizers; Junction; States; Light